O patrimônio geológico dos sistema praia - Plataforma da Costa Negra - Litoral oeste do Ceará - Rodrigues, Ana Alexandre Santos (2020)
The study of Geodiversity in beach and continental shelf environments, with a focus on geology and geomorphology, is of fundamental importance for its conservation and sustainable use. Research related to the inventory of Geological Heritage in the coastal zone is more frequent in beach environments, due to the feasibility of the researcher's direct contact with the object of study, leaving a gap of works of this nature on the continental shelf. The objective of this study is to identify the geosites that make up the Geological Heritage of the beach (geoforms / features) and platform (morphology / sedimentology) of the Costa NegraCearense (PCCNC), relating to the valuations and the provision of ecosystem services that these environments offer. The study area extends between the coastal plains of the municipalities of Itarema and Acaraú, until the break of the continental shelf, in the emerged portion the border points for the control of the study area are the Aracatimirim river (Itarema) and the sprawling wind farms ( Acaraú), while in the submerged environment it extends to the isobath of 10, with a distance of 10 to 15 km from the coast. The analysis of these systems takes place from the interpretation of data, on the beach through a characterization sheet of the places of interest, while on a platform they are acquired from techniques, such as bathymetry and geochemical analyzes of the sediments, to later be carried out. description and morphological / sedimentological characterization of the sectors.As a result, the scientific-educational, economic and environmental valuations that the beach and platform systems can provide through their respective ecosystem services are considered. In the beach environment, 11 geosites were highlighted, among them: beach sandstones, maludal and colluvial deposits, abrasion platform and types of dunes, which are directly related to the dynamic process-shape occurring on the coast, while in the platform sectors, highlighted the following geosites that are related to the present biodiversity and the conservation of sea resources in this ecosystem. Regarding the morphology, the presence of submerged canyons and dunes was detected, while the sedimentology of the platform occurred in two types, siliciclastic mainly with terrestrial and carbonate input from algae of the genus Halimeda and biota, and in some stretches the mixture of these two materials. In relation to chemical analyzes, the first obtained low levels in the evaluations, while the second obtained a more expressive result in these analyzes (organic matter and calcium carbonate).